Perencanaan Penukar Panas Tipe Coil sebagai Pemanas Air dengan Memanfaatkan Panas Gas Buang - Muhammad Irfansyah; Oleh Oleh; Iman Dirja (Jurnal Ilmiah Wahana Pendidikan, 2022)
The coil type heat exchanger is one of the important parts in the process of transferring heat from the exhaust heat to the water. This coil type heat exchanger has not been widely used in combustion exhaust gases. Heat transfer from gas to water in the coil is carried out by conduction and convection along the exhaust. The heat received by the water in the coil will change the liquid phase into steam and then the water vapor will naturally move to flow in the heat exchanger. The volume of water in the coil is half of the volume of the coil heat exchanger pipe. From the results of my research and simulations, the water in the water tank can be heated up to 82 oC. This heat exchanger is able to transfer heat from the hot water coming out of the heat exchanger in the exhaust into the water in the water tank (shell) as much as 2 liters. The final result of the calculation required a heat flow rate of 158.13 Watt.